ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN DEVIDEN (StudiEmpiris pada Perusahaan yang Tercatat di BEI Periode 2009-2011) (Students' Journal of Economic and Management, 2014)
This research is which testing factors current ratio, debt to equity ratio, growth, collateralizable assets, and return on equity which influence of DPR on company which listed on BEI (not banking and finance company). This research, we use purposive sampling. Had samples 18 companies by 446 companies which listed on BEI. Then that data are tasted by normality, multikolinearity, heteroskedasity and autokorelation. The next analysis we use double regretion to explain the connection of variables. The results show that the current ratio and growth not influence to DPR, DER and ROE influence negativly and significan to DPR, and COL influence possitifly and significan to DPR. Keyword: Devidend Payout Ratio, Current Ratio, Debt to Equity Ratio, Growth, Colateralizable Assets, and Return On Equity.